Low-lying dipole strength in the well-deformed nucleus 156Gd - Tamkas, M.; Aciksoez, E.; Isaak, J.; Beck, T.; Benouaret, N.; Bhike, M.; Boztosun, I.; Durusoy, A.; Gayer, U.; Krishichayan; Loeher, B.; Pietralla, N.; et al. (ELSEVIER SCIENCE BV, 2019)
The low-lying dipole strength of the deformed nucleus Gd-156 was investigated in the energy region from 3.1 MeV to 6.2 MeV using the method of nuclear resonance fluorescence (NRF). The NRF experiments were performed at the Darmstadt High Intensity Photon Setup (DHIPS) at Technische Universitat Darmstadt using unpolarized continuous-energy bremsstrahlung and at the High-Intensity gamma-ray Source (HI gamma S) at Duke University using quasi-monoenergetic and linearly-polarized photon beams. The combination of both experiments allows to separate electric and magnetic contributions and to determine absolute transition strengths for individual excited states as well as averaged quantities over narrow excitation energy regions. The investigated energy regions cover the region of the scissors mode as well as the low-energy part of the Pygmy Dipole Resonance. This is the first experiment where both of these excitation modes as well as the region in between has been successfully studied in a deformed heavy nucleus using the NRF method. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Nuclear resonance fluorescence; gamma-ray spectroscopy; Quasi-monochromatic photon source; Deformed nuclei; Dipole strength distribution; Pygmy dipole resonance; MODES; PYGMY; EXCITATIONS; Physics